The Effect of Government Policy on the Principal Tasks of Teachers as Current Educators - Mirza Ghulamudin (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Education is a bridge for humans to live their lives in the future. Students will gain knowledge in learning activities in schools. In addition to knowledge, students will also form the characters formed by the teacher in learning activities. The role of the teacher is indeed very influential for the development of students, in addition to providing knowledge. A difficult task must be carried out by a teacher. Is the government policy appropriate or even burden the main tasks of teachers who should focus on delivering subject matter, building moral character? Nowadays, the teacher's task tends to compile reports, making so many administrations. Eventually there were many cases of teachers leaving the class, due to administrative work that was piling up. In this study, the researcher used 20 (twenty) samples of teachers who had become Civil Servants. Many of them are complaining about administrative tasks that are too much, because it is very difficult to divide up the work time and time to face to face with students. The teachers really hope that the Government of Indonesia revises its policy to reorganize so that the administrative tasks of the teacher are not too many, and the main tasks of the teacher can be carried out appropriately, namely face to face with students in presenting the subject matter and forming a good personality.Keywords: Government Policy, teacher's main tasks